Application of Interactive Multimedia-Based Mathematics Learning Media to Increase Students' Interest in Learning - Dwianti Putri Amelia; Amin Harahap (Budapest International Research and Critics University, 2021)
This study aims to overcome students' low interest in learning mathematics by using interactive multimedia learning models to increase students' interest in learning mathematics in class VII MTS PP ATH-TOHIRIYAH Gunung Selamat in the midst of the Corona Virus outbreak. With the application of this interactive multimedia learning model, it is hoped that it will increase students' interest in learning mathematics. The research method used in this study is a quantitative method with a class action method. In this study, the authors analyzed the data from the pre-test and post-test scores from both classes. The population in this study were all students of MTS PP ATH-TOHIRIYAH Gunung Selamat grade VII, totaling 40 students. The sampling technique used is probability sampling using cluster sampling. From the results of data analysis, it is known that there is a difference between the average value of student learning outcomes before and after the implementation where the average value of the experimental pre-test is 56.60% and the control pre-test is 66.70% and becomes 86.55% for the experimental post-test and 75.30% for the control post-test. The experimental class increased by 29.95%, while the control class only increased by 8.60%. Based on the results of research and data processing that have been discussed, it can be concluded that the application of the interactive multimedia-based mathematics learning process has an impact on student learning interest in terms of student learning outcomes.